ANTHROPONYMS AND NATIONAL IDENTITY: LINGUISTIC FOUNDATIONS OF ASSESSING ETHNICITY THROUGH NAMES - Qobilov Mirziyo Eshnozar ogli (Western European Studies, 2025)
This article systematically analyzes the relationship between anthroponymy and national identity from a linguistic point of view, how ethnicity and national identity are reflected in the name, highlighting the interaction of Turkic, Persian-Tajik, Slavic and Arabic theophoric layers, writing traditions and formalization practices, as well as examining the possibility of transethnicity and error. The article presents etymological analysis, sociolinguistic observations and statistical standards as a methodological basis, and gives examples of Uzbek, Tajik, Kazakh, Kyrgyz and Russian-Slavic anthroponyms as examples.
Keywords: Anthroponymy; national identity; ethnolinguistics